Smart Card Implementation In Malaysia : How Well The Users Are Accepting The Technology - Abd. Rahim, Muhd Khairulidzwan (2005)
The issues are mainly focused on the readiness of other parties to accept MyKad as a Medium for several important clarification mechanisms that deals with the goverment as well as other profit and non-profit organizations. This has shown that the smard card technology which has huge capabilities has not yet being fully utilized by Malaysians. The research paper will consider these issues in order to find out the reality above the matter of readiness of accepting new ways as well as to come out with the solutions on making smart card as a way of Malaysians' lifestle through the literature reviews and questionnaire surveys to collect data from the end users in despite the demographic boundaries.